Imagine There is no Death… : Soviet Funeral Reforming en Marche - Sokolova, Anna (Temenos - Nordic Journal for the Study of Religion, 2023)
The idea of human mortality and the funerary practices that derive from it seems to be one of the most enduring aspects of culture. What if we stated that death means nothing but pure organic decomposing, leaving nothing behind but the chemical constituents? What if such an approach became the basis of an active reformatory policy of a state? Soviet practices of death and attitudes toward dead bodies can be mentioned among the most significant changes that have taken place in Russian society over the past 150 years. While Soviet leaders have been given lavish state funerals, the death of an ‘average’ person has become less and less visible. Although the state made considerable efforts to reform the funeral sphere, this did not lead to the development and enhancement of brand-new funeral rituals. Rather this policy gradually diminished the social value of funerals and facilitated a transition to DIY funerals. Following Robert Hertz and Arnold van Gennep, I consider funerary practices as a social phenomenon and a social mechanism that allows society and its members to adapt to mortality, experience loss, and restore their integrity. In my talk, I will show how a new understanding of human nature and human mortality transformed the social fabric of Soviet society. Will the lecture be based on my recently published book ‘A New Death for a New Man? Funeral Culture of Early USSR’.